The Effectiveness of Using Cake-Learning Application on Students’ Vocabulary Mastery At MA Nurul Habibi NW Liwung - M. Alwan Hadi; Muliani; Tawali (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This research is aimed to investigate the effectiveness of utilizing the CAKE-Learning Application in enhancing students' vocabulary mastery at MA Nurul Habibi Nahdlatul Wathan Liwung in academic year 2023/2024. The objective of the study was to know whether the CAKE-Learning Application is an effective tool to improve students' vocabulary mastery. The design of research method used pre-experimental study or quantitative method. The subject of the study was second grade student of MA Nurul Habibi Nahdlatul Wathan Liwung, consist of seven female students. The technique of collecting the data were pre-test and post-test. The instrument of the research used written test in the form of multiple choice. The procedure to analyze data were mean score, mode, median, and t-test was used according to Sudijono, 2007: 22. The data was analyzed using statistical formula of t-test. The result of data analysis showed that the value of t-test was 9.756 and t-table 1.501 so the value of t-test is higher than t-table in significance level of 005 ((95%) with degree of freedom 7. It means that t-critical value was significant for this confidence level. And alternative hypothesis (Ha) was accepted and null hypothesis (Ho) was rejected. Therefore, it could be concluded that there was effective of using Cake-Learning Application on students’ vocabulary mastery at MA Nurul Habibi Nahdlatul Wathan Liwung in Academic Year 2023/2024.